Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Test: 15

Answer

$x ( 1 - x) (1+x) ( 1 + x^2)$

Work Step by Step

$x - x^5 = x ( 1 - x^4 ) = x ( (1)^2 - (x^2 ) ^2 ) = x ( 1 - x^2) ( 1 + x^2) = x ( (1)^2 - (x)^2) ( 1 + x^2) = x ( 1 - x) (1+x) ( 1 + x^2)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.